Integrating Artificial Intelligence Into Financial and Strategic Frameworks: A Path To Entrepreneurial Success In Emerging Markets - Oktaria Ardika Putri (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines the role of Artificial Intelligence (AI) in enhancing financial management, strategic planning, and entrepreneurial success among startups operating in emerging markets, specifically Indonesia. Grounded in the Dynamic Capabilities Theory, this research investigates how AI-driven financial tools and strategic frameworks mediate operational efficiency to produce entrepreneurial growth. An explanatory sequential mixed-methods design was employed, consisting of a quantitative phase surveying 200 Indonesian startups analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), followed by qualitative in-depth interviews with four key informants. The quantitative results reveal that AI integration in financial management (? = 0.312, p < 0.001) and AI-driven strategic planning (? = 0.287, p < 0.001) significantly influence entrepreneurial success, explaining 52.4% of the variance (R² = 0.524). Operational efficiency mediates the relationship between strategic planning and entrepreneurial success (? indirect = 0.099, p < 0.01). Qualitative findings corroborate these results, highlighting practical challenges and contextual enablers of AI adoption. This study contributes to the entrepreneurship literature by extending Teece's dynamic capabilities framework into the AI-driven startup ecosystem of emerging economies, offering both theoretical and managerial implications for sustainable business growth.